A Ten-year retrospection of the behavior of Russian stock returns - Stanislav Anatolyev (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
We study three aspects of the Russian stock market - factors influencing stock returns, integration of the stock market with world .financial markets, and market efficiency - from 1995 to present, putting emphasis on how these evolved over time.We .find many highly unstable relationships, and indeed, greater instability than that generated by financial crises alone.While most computed statistics exhibit constant ups and downs, there are recently clear tendencies in the development of the Russian stock market: a sharp rise in explainability of returns, an increased role of international financial markets, and a decrease in the profitability of trading.
URN:NBN:fi:bof-201408072206
Keywords: C22; F36; G14; G15; 330; Russia; transition; stock returns; integration; efficiency